Development of Pre-Service Early Childhood Teachers' Technology Integrations Skills Through a Praxeological Approach - Kulaksız, Taibe; TORAN, MEHMET (Springer, 2022)
How to improve and what should be carried out for pre-service teachers' technological competencies for teaching purposes is still an important issue on the agenda of the higher education field. In light of this, we aimed to reflect the individual and collective technology integration knowledge and skills construction process of pre-service early childhood education teachers with democratic participation. We utilized the praxeological approach as a method and learning approach to reveal the reflections of the instructional technologies course. The participants in this study were 52 sophomore pre-service teachers in the early childhood education department. We collected the data from various sources such as interviews, portfolios, researchers' field notes, e-mails, online course evaluation form. We carried out the thematic analysis method to analyze the data. The findings indicated that three main themes emerged as initial challenges, learning process, and learning outcomes during enhancement of pre-service early childhood teachers' technology integration knowledge and skills. As a result, the praxeological approach used in instructional technologies courses in teacher education programs leads to a crucial digital transformation to be ready to become future teachers.
Keywords: Instructional Technology; Pre-service Teachers; Technology Integration; Early Childhood Education; Praxeological Research